Loss of GCN5L1 in cardiac cells disrupts glucose metabolism and promotes cell death via reduced Akt/mTORC2 signaling. Issue 12 (19th June 2019) - Manning, Janet R.; Thapa, Dharendra; Zhang, Manling; Stoner, Michael W.; Traba, Javier; Corey, Catherine; Shiva, Sruti; Sack, Michael N.; Scott, Iain
Abstract : GCN5L1 regulates protein acetylation and mitochondrial energy metabolism in diverse cell types. In the heart, loss of GCN5L1 sensitizes the myocardium to injury from exposure to nutritional excess and ischemia/reperfusion injury. This phenotype is associated with the reduced acetylation of metabolic enzymes and elevated mitochondrial reactive oxygen species (ROS) generation, although the direct molecular targets of GCN5L1 remain largely unknown. In this study, we sought to determine the mechanism by which GCN5L1 impacts energy substrate utilization and mitochondrial health. We find that hypoxia and reoxygenation (H/R) leads to a reduction in cell viability and Akt phosphorylation in GCN5L1 knockdown AC16 cardiomyocytes, in parallel with elevated glucose utilization and impaired fatty acid use. We demonstrate that glycolysis is uncoupled from glucose oxidation under normoxic conditions in GCN5L1-depleted cells. We show that GCN5L1 directly binds to the Akt-activating mTORC2 component Rictor, and that loss of Rictor acetylation is evident in GCN5L1 knockdown cells. Finally, we show that restoring Rictor acetylation in GCN5L1-depleted cells reduces mitochondrial ROS generation and increases cell survival in response to H/R. These studies suggest that GCN5L1 may play a central role in energy substrate metabolism and cell survival via the regulation of Akt/mTORC2 signaling.